Pneumopericardium due to ingestion of button battery - Jai Prakash Soni; Sandeep Choudhary; Pramod Sharma; Mohan Makwana (Wolters Kluwer Medknow Publications, 2016)
Mostly ingested button batteries passed through the gastrointestinal tract without any adverse effects. But button battery can lead to hazardous complications including tracheoesophageal fistula (TEF), especially when the battery is impacted in the esophagus. Urgent esophagoscopic removal of the battery is essential in all cases. Once the TEF is identified, conservative management is the initial treatment of choice. Delayed primary repair can be tried if spontaneous closure does not occur. Here in we want to report a rare case of air leak syndrome, pneumo-pericardium secondary to the corrosive effect of a button battery and child recovered completely with conservative management.